2018
DOI: 10.47363/pms/2018(2)112
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and health beliefs of elderly women toward osteoporosis in Mansoura, Egypt

Abstract: Background: Osteoporosis is among the top five conditions causing disability for elder, particularly in women. Unfortunately, Egyptian women were reported to have a lower bone mineral density compared to their Western counterparts. So, this study was conducted to assessed knowledge and beliefs of menopausal women about osteoporosis and their possible associated factors. Methods: A cross-sectional study was conducted on 208 menopausal women recruited from both rural and urban settings, Mansoura, Egypt. A questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…In Jager et al (2020) study evaluating the effectiveness of CBT in a randomized clinical trial, the authors used several scales and reported that 37% of their 54 patients showed statistical improvement (Jager et al, 2020). It is important to note that Jarger's study is so far the only publication that presents results of a randomized clinical trial (RCT) for misophonia while our results represent a Level IV of evidence (Series of Cases) and as such are not as strong as RCT (Level II) (Poehling, 2004;Burns et al, 2011;El-Gilany, 2018).…”
Section: Comments On Other Proposed Approaches To Misophonia and The ...mentioning
confidence: 77%
See 4 more Smart Citations
“…In Jager et al (2020) study evaluating the effectiveness of CBT in a randomized clinical trial, the authors used several scales and reported that 37% of their 54 patients showed statistical improvement (Jager et al, 2020). It is important to note that Jarger's study is so far the only publication that presents results of a randomized clinical trial (RCT) for misophonia while our results represent a Level IV of evidence (Series of Cases) and as such are not as strong as RCT (Level II) (Poehling, 2004;Burns et al, 2011;El-Gilany, 2018).…”
Section: Comments On Other Proposed Approaches To Misophonia and The ...mentioning
confidence: 77%
“…Results obtained from 201 consecutive patients with DST showed an over 80% success rate without relapse (Jastreboff and Jastreboff, 2014b) and provided additional support to the presented model. However, we realize the limitations of reported results: 1) the lack of a control group, 2) the assessment of improvement was done based on Likert scales of our initial and follow-up questionnaires, and 3) results were not collected in a clinical trial and belongs to category case series (Level IV of clinical validity) (Poehling, 2004;Burns et al, 2011;El-Gilany, 2018).…”
Section: Critical Assessment Of the Results Of Trt Treatmentmentioning
confidence: 99%
See 3 more Smart Citations